3D Printing Technology in Education and Some Examples of 3D Printer Technology Materials Applied in Chemistry Education - ŞİMŞİR, Nazan; ÜNAL, Ahmet; AKYÜZ, Halil İbrahim; YERLİKAYA, Zekeriya (Yildiz Teknik University - Uluslararasi Alan Egitimi Dergisi, 2021)
Technology affects and changes our lives day by day. The application of technological developments and advances in education is of great importance in order to bring targeted behavior to individuals. One of the technologies we observe in many areas, including education, is three-dimensional (3D) printing technology. Three dimensional printers can be used in the field of education to better visualize complex structures. 3D printers have a truly groundbreaking technology in solid modeling. With this technology, individuals can realize their dreams in a short time and in a concrete way. 3D printing technology also shows tremendous potential in the chemical sciences. This type of technology has begun to enter chemistry education on a wide range of subjects, and chemistry models produced in educational processes such as symmetry and point group theory, unit cell theory, orbital theory and structure-energy relationships contribute to students in terms of vision, touch and detailed examination. In this study, together with general information about the use of 3D printer technology in education, the importance of using this technology in education and information about the materials used in the field of chemistry teaching produced with 3D printer technology are presented.
Keywords: 4. Education; 8. Economic growth; 7. Clean energy